2017
DOI: 10.1071/an15633
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and physicochemical properties of red tilapia (Oreochromis niloticus) surimi gel as affected by microbial transglutaminase

Abstract: Thermal and physicochemical properties of red tilapia (Oreochromis niloticus) surimi gel incorporated with different levels of microbial transglutaminase (MTGase) were investigated. Surimi samples mixed with various concentrations of MTGase were subjected to two-stages heating (at 45°C followed by 90°C) to prepare surimi gel. Samples formulated with 0.30 MTGase (units/g surimi) showed the highest breaking force and deformation, and lowest expressible water content among treatments. Highest storage modulus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 39 publications
4
39
0
2
Order By: Relevance
“…At the same time, the results have also shown that increasing the rate of excess transglutaminase results in a breakdown of the gel structure of the product. These results are in accord with those obtained by Jiang et al (2000) who reported that the gel structure of surimi gels from threadfin bream (Nemipterus virgatus) and pollock (Rastrelliger kanagurta) increased when transglutaminase increased up to a certain level, and a further increase in transglutaminase decreased the gel structure of the product (Seighalani et al, 2017).…”
Section: The Role Of Transglutaminase Supplementation and Incubation supporting
confidence: 92%
See 3 more Smart Citations
“…At the same time, the results have also shown that increasing the rate of excess transglutaminase results in a breakdown of the gel structure of the product. These results are in accord with those obtained by Jiang et al (2000) who reported that the gel structure of surimi gels from threadfin bream (Nemipterus virgatus) and pollock (Rastrelliger kanagurta) increased when transglutaminase increased up to a certain level, and a further increase in transglutaminase decreased the gel structure of the product (Seighalani et al, 2017).…”
Section: The Role Of Transglutaminase Supplementation and Incubation supporting
confidence: 92%
“…The study by Seighalani et al (2017), and Duangmal and Taluengphol (2010) also showed similar results with transglutaminase supplementation at 0.3 U/g surimi and 3 g/kg surimi, respectively. As transglutaminase catalyzes the cross-linking reaction of myosin and leads to the formation of protein intra-and intermolecular covalent bonds, it was concluded that differences in the whiteness value could correspond to the increased turbidity of gels because of transglutaminase activity.…”
Section: The Role Of Transglutaminase Supplementation and Incubation supporting
confidence: 52%
See 2 more Smart Citations
“…Those products include sh balls, sh cakes, crab meat analogues, etc. 3 The prime factor in achieving the desired texture is the gel-forming ability of myobrillar sh proteins. 4 The textural property of gel is the most important attribute, which determines the price of surimi.…”
Section: Introductionmentioning
confidence: 99%